2022
DOI: 10.3389/fnut.2022.1025919
|View full text |Cite
|
Sign up to set email alerts
|

Time-restricted eating for patients with diabetes and prediabetes: A systematic review

Abstract: BackgroundSeveral studies have explored the effect of time-restricted eating (TRE) on patients with diabetes and prediabetes. However, these studies have not been analyzed and summarized as a whole. We conducted a systematic review to summarize and analyze all studies about the efficacy and safety of TRE for patients with diabetes and prediabetes.MethodsWe conducted a comprehensive search of the Embase, PubMed and Cochrane databases and the time span was from inception to 1 May 2022. The Cochrane Collaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…With no serious adverse effects, TRE may lead to weight loss as well as improvements in insulin sensitivity and plasma glucose. For patients with diabetes and prediabetes, time-restricted eating is a safe and practical intervention that may improve metabolism and the cardiovascular system [16].…”
Section: Discussionmentioning
confidence: 99%
“…With no serious adverse effects, TRE may lead to weight loss as well as improvements in insulin sensitivity and plasma glucose. For patients with diabetes and prediabetes, time-restricted eating is a safe and practical intervention that may improve metabolism and the cardiovascular system [16].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the PICOS framework ( 52 ), the inclusion criteria for this systematic review were meticulously established as follows: (P) patients, encompassing individuals diagnosed with NAFLD; (I) intervention, specifically focusing on time-restricted eating (TRE); (C) control, which included several comparative conditions such as calorie restriction (CR), habitual meal timing, alternate-day fasting (ADF), or a standard diet; (O) outcomes, with primary endpoints being the effects of TRE on liver parameters in NAFLD patients and secondary outcomes including alterations in body weight, plasma lipid levels, body composition, insulin resistance, glucoregulatory factors, inflammation parameters (cytokeratin and high-sensitivity C-reactive protein), and the safety profile of TRE; and (S) study type, which was RCTs. Exclusions were made for editorials, duplicates, comments, conference abstracts, and case reports.…”
Section: Methodsmentioning
confidence: 99%
“…TRE may be particularly useful in societies of today where constant access to food might contribute to disturbance of circadian rhythms and have adverse effects on cardiometabolic health [10][11][12]. Reviews that mainly include studies of shorter duration (<16 weeks) have suggested that TRE is associated with modest weight loss and improved body composition, metabolic markers, and appetite regulation in people with overweight, obesity, prediabetes, and T2D [7,8,10,[13][14][15]. The metabolic syndrome is highly prevalent and is associated with an increased risk of T2D and cardiovascular disease [16].…”
Section: Introductionmentioning
confidence: 99%